Factors Influencing Choice of Islamic Digital Banking: Opportunity or Challenge for the Islamic Finance Industry? - Riza, Alex Fahrur; Khoiruddin, Akhmad Yusuf; Ibrahim, Muhammad Hanif (FEBI UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose - This study aims to test the TAM model to determine people's perceptions of digital banking. Although empirical research has been conducted on the introduction of digital banking, this is still minimal in the Islamic banking context, as the use of digital banking in Islamic banks is still new.Design/methodology –This study is descriptive and quantitative using survey methods to measure an individual's perception of digital banking in Islamic banks. The survey contains closed and open-ended questions to measure the perception of mobile banking users based on the Technology Acceptance Model (TAM). This survey uses a voluntary survey of respondents scattered across different cities in Indonesia. Data analysis uses SEMPLS 7.0 and SPSS23.Findings -Originality - In addition to testing the TAM digital banking model of the original Islamic bank, this study also examines the potential for new variables that emerge from customer perceptions and uses the data to create new unique to Shariah's recruitment-based banks. We propose variables / models according to the technology. We will also consider obstacles to the introduction of digital banking by Islamic banks.